The Diversity of Character Names in the Begalan Tradition in Purbalingga Regency - Tri Okviana Rahmawati; Elen Inderasari (2025)
Purbalingga Regency has a variety of traditions, one of which is still preserved is the Begalan tradition in Banyumasan wedding customs. The Begalan tradition has diverse names of characters and has not been scientifically documented. Therefore, this study aims to determine the diversity of names of characters in the Begalan tradition as well as their contextual and cultural meanings. This study uses a qualitative ethnographic model method with a contextual semantic approach. The data sources in this study are the actors of the Begalan community. Data collection was carried out through interviews, observation, and documentation. Data validity techniques use triangulation of data sources and methods. Data were analyzed using ethnographic analysis methods. The results of this study found 2 types of characters, namely protagonists and antagonists. 4 names of protagonists and 5 names of antagonists were found. The names of the protagonists are Ki Surantani, Jaka Rosa, Ana, and Duta Sura. The names of the antagonists are Joko Lelono, Jaka Sundang, Alif, Suro Dendo, and Suradenta. In the naming of these figures, there are 3 aspects that underlie why they were sent, namely based on orders, duties, and symbols. Contextual and cultural meanings were also found in each character's name. The contextual meanings found were in the form of involvement in the situation/role of the character, the actions of the involvement, and other relevant characteristics of the situation, namely objects in the Begalan tradition. Contextual meanings are dominated by involvement in the situation/role of the character. Meanwhile, the cultural meanings contained in the names of the Begalan traditional figures are quite diverse, namely associated with stories of ancient figures, the character of the Banyumasan wong, the courage of Javanese women, the nature of responsibility of ancient Javanese people, and the religious meanings contained in brenong kepang. Cultural meanings are dominated by stories of ancient figures.